Sustained Clinical Improvement in a Subset of Patients With Progressive Multiple Sclerosis Treated With Epstein–Barr Virus-Specific T Cell Therapy - Ioannides, Zara A.; Csurhes, Peter A.; Douglas, Nanette L.; Mackenroth, Gem; Swayne, Andrew; Thompson, Kate M.; Hopkins, Tracey J.; Green, Kerryn A.; Blum, Stefan; Hooper, Kaye D.; Wyssusek, Kerstin H.; Coulthard, Alan; et al. (Frontiers in Neurology, 2021)
Background: Increasing evidence indicates a role for Epstein–Barr virus (EBV) in the pathogenesis of multiple sclerosis (MS). EBV-infected autoreactive B cells might accumulate in the central nervous system because of defective cytotoxic CD8+ T cell immunity. We have previously reported results of a phase I clinical trial of autologous EBV-specific T cell therapy in MS 6 months after treatment. Objective: To investigate longer-term outcomes in MS patients who received autologous EBV-specific T cell therapy. Methods: We assessed participants 2 and 3 years after completion of T cell therapy. Results: We collected data from all 10 treated participants at year 2 and from 9 participants at year 3. No serious treatment-related adverse events were observed. Four participants had at least some sustained clinical improvement at year 2, including reduced fatigue in three participants and reduced Expanded Disability Status Scale score in two participants. Three participants experienced a sustained improvement in at least some symptoms at year 3. More sustained improvement was associated with higher EBV-specific CD8+ T cell reactivity in the administered T cell product. Conclusion: Autologous EBV-specific T cell therapy is well tolerated, and some degree of clinical improvement can be sustained for up to 3 years after treatment.